Fire Risk Assessment of Adaptive Re-Use of Historic Shop Houses for Sleeping Accommodations in Malaysia - Mydin, M.A.O.; Arminda, W.; Sani, N. Md. (EDP Sciences, 2014)
Heritage buildings were generally constructed without regard for fire risks or the requirements for fire protection, as are obligatory in new constructions. When a heritage building undergoes a change to its original function, improvements to the building’s fire safety are necessary to meet the needs of possible increases in occupancy loads and to account for fire risks related to the new usage. This research focuses on fire safety risks, fire protection and safety systems as well as the rules and regulations that an adaptive reuse heritage shop house is bound to when transitioning to a sleeping accommodation, which, in this case, means becoming a hotel. In this research, six heritage shop houses were chosen as case studies. The objectives of this research were to evaluate current fire emergency plans as well as to identify and assess possible fire hazards created by adaptive reuse of heritage shop houses to sleeping accommodations in Penang through a series of observations and interviews. The results of the research show that most of the buildings were provided with inadequate fire safety systems.